CHARACTERISTICS AND ANALYSIS OF INTELLECTUL NOVELS IN LITERATURE - Ruzieva, Dilfuza (Журнал иностранных языков и лингвистики, 2021)
Background. It is well known that literature is a genre that is relative in terms of its purpose, related to their art. Fiction, as a complex synthesis of art forms, is constantly updated and perfected throughout its development; just artistic Word fans have come up with unexpected ideas, themes, forms, and contents that have caught the attention of many fields. Methods. Word fans have come up with unexpected ideas, themes, forms, and contents that have caught the attention of many fields, not just philosophy, politics, sociology, psychology, and even the exact sciences, such as medicine. Albert Einstein, the founder of the universal theory of relativity, acknowledges the great importance that the works of Fyodor Dostoevsky played in the realization of his discovery. Homer’s Iliad, Firdavsi’s Shahnameh, Dante’s Divine Comedy, Zahriddin Bobur’s Boburnoma, Goethe’s Faust, Tolstoy’s War and Peace, Dostoevsky’s Crime and Punishment, Chingiz Aitmatov’s The Signs of the End Times There are still differences, sometimes even contradictions.